Biodegradable zinc alloys with high strength and suitable mechanical integrity as bone repair metals - Chengwu Lu; Chao Song; Yunlong Yu; Linhai Yang; Wu Zheng; Fenqi Luo; Yuhua Xiao; Jun Luo; Jie Xu (Scientific Reports)
Abstract Mechanical properties and integrity of biodegradable Zn alloys during degradation holds significant importance. In this study, a Zn-Mg-Mn alloy with tensile strength of 414 MPa and an elongation of 26% was developed. The strength contributions of as-extruded Zn alloy from grain boundary strengthening, precipitation strengthening, and second phase strengthening. Degradation of the Zn alloy in Hank’s solution exhibited a decreasing trend with prolonged immersion, eventually stabilizing at 16 μm/year. Corrosion morphology analysis revealed that the corrosion modes transformed from pitting corrosion to severely localized corrosion with prolonged immersion time, eventually lead to formation of large holes. Although the tensile strength of the Zn alloys remained relatively unchanged following varied immersion time, a substantial decrease in elongation was observed. The decreased elongation primarily attributed to the formation of surface corrosion pits or holes, exacerbating crack propagation during tension. Biocompatibility assessments of Zn alloys demonstrated that a 50% concentration of Zn alloy leach solution cultured with C3H10 and RMSC cells yielded cellular activity exceeding 80%, indicating excellent cytocompatibility. Alkaline phosphatase (ALP) and alizarin red staining results further underscored the remarkable early and late osteogenic properties exhibited by Zn-Mg-Mn alloy.